Students' Mathematical Connections in Solving Word Problems Based on Polya's Stages - Oktavianus Rudi Sutardi; Lathiful Anwar; Makbul Muksar (PRISMA, 2026)
The purpose of this study was to describe the mathematical connection ability of grade XI students in solving story problems of linear equations of three variables in terms of problem solving steps according to Polya. The method used in this research is qualitative research. Student connection data was collected using tests and interviews. Then the students' connection data were analyzed based on three types of connections, namely modeling connections, connections between concepts and procedure connections. The results showed that the modeling connection process occurred in the understand the problem and carry out the plan steps. The connection process between concepts occurs at the device a plane and carry out the plan steps. While the procedural connection in the carry out the plan and look back steps.  Students' mathematical connection skills are shown in translating problems into mathematical models, connecting between mathematical concepts and procedures. The connection component that has not been mastered by students is not understanding the concept of simplifying equations by grouping similar terms. Students tend to use the operation of moving segments in simplifying the equation.